Identifying factors of activities of daily living important for cost and caregiver outcomes in Alzheimer's disease. (26th August 2015) - Reed, Catherine; Belger, Mark; Vellas, Bruno; Andrews, Jeffrey Scott; Argimon, Josep M.; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W.; Wimo, Anders; Haro, Josep Maria
ABSTRACT: Background: We aimed to obtain a better understanding of how different aspects of patient functioning affect key cost and caregiver outcomes in Alzheimer's disease (AD). Methods: Baseline data from a prospective observational study of community-living AD patients (GERAS) were used. Functioning was assessed using the Alzheimer's Disease Cooperative Study – Activities of Daily Living Scale. Generalized linear models were conducted to analyze the relationship between scores for total activities of daily living (ADL), basic ADL (BADL), instrumental ADL (IADL), ADL subdomains (confirmed through factor analysis) and individual ADL questions, and total societal costs, patient healthcare and social care costs, total and supervision caregiver time, and caregiver burden. Results: Four distinct ADL subdomains were confirmed: basic activities, domestic/household activities, communication, and outside activities. Higher total societal costs were associated with impairments in all aspects of ADL, including all subdomains; patient costs were associated with total ADL and BADL, and basic activities subdomain scores. Both total and supervision caregiver hours were associated with total ADL and IADL scores, and domestic/household and outside activities subdomain scores (greater hours associated with greater functional impairments). There was no association between caregiver burden and BADL or basic activities subdomain scores. The relationship between total ADL, IADL, and the outside activities subdomain and outcomes differed between patients with mild and moderate-to-severe AD. Conclusions: Identification of ADL subdomains may lead to a better understanding of the association between patient function and costs and caregiver outcomes at different stages of AD, in particular the outside activities subdomain within mild AD.